Discovery and description of a deeply divergent frog lineage of the genus Minervarya Dubois, Ohler & Biju, 2001 (Anura: Dicroglossidae) from the basaltic plateau of the northern Western Ghats, Maharashtra, India - Yadav, Omkar; Bhosale, Amrut; Patil, Priyanka; Khandekar, Akshay; Dinesh, K.p. (Zootaxa, 2025)
A new species of dicroglossid frog Minervarya ghatiborealis sp. nov. is described from the Mahabaleshwar region of the northern Western Ghats, India, based on multiple axis of evidences like morphological, acoustics, genetic datasets, and geographical isolation. The new species is phenotypically distinct from its congeners by a combination of morphological characters: body large, robust, with SVL 55.0–59.1 mm (n = 5) in adult males and SVL 67.1 mm (n = 1) in adult female; sub-elliptical snout; rudimentary webbing; dorsal skin glandular with highly ridged folds. Phylogenetically, the new species exhibits sister relationship to the clade containing Minervarya goemchi, M. mysorensis and M. brevipalmata. Genetic distance between the new species and the members of its sister clade varies from 6.5% to 7.2% for DNA sequences of the mitochondrial 16S rRNA gene. For the nuclear-encoded Tyrosinase gene genetic distance between the new species and its syntopic, large-bodied, congener M. goemchi is 1.4%. Additionally, an advertisement call description is provided to differentiate the new species from its congeners. The importance of the Mahabaleshwar plateau and altitudinal preferences of large-sized Minervarya frogs in the northern Western Ghats are discussed.